2007
DOI: 10.1111/j.1471-4159.2007.04682.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of matrix metalloproteinase inhibition on short‐ and long‐term plasticity of schaffer collateral/CA1 synapses

Abstract: It is increasingly evident that matrix metalloproteinases (MMPs), a family of zinc containing extracellular endopeptidases, participate in processes supporting hippocampal synaptic plasticity. The purpose of this study was to further the understanding of MMPs involvement in hippocampal plasticity. Acute hippocampal slices, generated from 20- to 30-day-old male Sprague-Dawley rats, were subjected to various electrophysiologic stimulatory paradigms to produce either short-term or long-term modifications to synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
102
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 28 publications
11
102
2
Order By: Relevance
“…It is notable that recent measurements in the intact hippocampal mossy fiber-CA3 projection, showed that MMP inhibition did not alter PPF, but did reduce LTP in the first minutes following HFS (Wojtowicz and Mozrzymas, 2010). While the importance of MMP mediation in Schaffer collateral PPF is controversial (Meighan et al, 2007;Nagy et al, 2006), our results suggest that in the complex TBI + BEC insult, MMPs have less influence on PPF short-term plasticity. Collectively, our electrophysiological data are consistent with the hypothesis that postsynaptic activity may be more vulnerable to changes in ADAM-10/Ncadherin expression, preferentially contributing to greater deficits in synaptic efficacy under maladaptive conditions.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…It is notable that recent measurements in the intact hippocampal mossy fiber-CA3 projection, showed that MMP inhibition did not alter PPF, but did reduce LTP in the first minutes following HFS (Wojtowicz and Mozrzymas, 2010). While the importance of MMP mediation in Schaffer collateral PPF is controversial (Meighan et al, 2007;Nagy et al, 2006), our results suggest that in the complex TBI + BEC insult, MMPs have less influence on PPF short-term plasticity. Collectively, our electrophysiological data are consistent with the hypothesis that postsynaptic activity may be more vulnerable to changes in ADAM-10/Ncadherin expression, preferentially contributing to greater deficits in synaptic efficacy under maladaptive conditions.…”
Section: Discussioncontrasting
confidence: 51%
“…It is also possible that collateral inhibition of the secreted MMPs 3 and 9 contributes to the attenuated LTP response reported here. While each of these MMPs has been shown to support LTP maintenance and synaptic stability (Conant et al, 2010;Meighan et al, 2007;Nagy et al, 2006;Wang et al, 2000), such effects were demonstrated by the application of MMP inhibitors at the time of LTP trials, conditions that do not directly address the timedependent processes of the present experimental paradigm. A more likely explanation of the effect of GM6001 on LTP would be that it attenuates ADAM-10 lytic shedding of N-cadherin, thereby increasing stabilization of the post-synaptic density (Isaac et al, 1995;Liao et al, 1995), and facilitating the trafficking of synaptic AMPA receptors (Bredt and Nicoll, 2003;Malenka and Nicoll, 1999;Nuriya and Huganir, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…It has been shown that MMP-9 is rapidly and transiently activated in an NMDA receptor-and a protein synthesis-dependent manner during the late phase of long-term potentiation (LTP) (Nagy et al, 2006). MMP-9 is activated perisynaptically after LTP induction and is required for LTP maintenance (Bozdagi et al, 2007;Meighan et al, 2007;Okulski et al, 2007). Recent studies indicate also the important role of MMP-9 in shaping dendritic spine morphology (Wang et al, 2008;Bilousova et al, 2009;Michaluk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In brain, they are secreted by neurons and glia in an inactive (pro) form, and they become proteolytically active when several regulatory steps that result in removal of the propeptide are triggered in response to specific stimuli (9). For example, studies have shown that in response to LTP induction, MMP-9 rapidly becomes proteolytically active at perisynaptic sites and essential for maintenance of LTP (10)(11)(12)(13). Thus, perisynaptic MMP-9 proteolysis in response to LTP induction may be critical for local remodeling of dendritic spine structure and function necessary to support long-term synaptic plasticity.…”
mentioning
confidence: 99%